Feasibility and acceptance of electronic quality of life assessment in general practice: an implementation study - Rogausch, Anja; Sigle, Jörg; Seibert, Anna; Thüring, Sabine; Kochen, Michael M; Himmel, Wolfgang (Health and quality of life outcomes, 2009)
Background Patients' health related quality of life (HRQoL) has rarely been systematically monitored in general practice. Electronic tools and practice training might facilitate the routine application of HRQoL questionnaires. Thorough piloting of innovative procedures is strongly recommended before the conduction of large-scale studies. Therefore, we aimed to assess i) the feasibility and acceptance of HRQoL assessment using tablet computers in general practice, ii) the perceived practical utility of HRQoL results and iii) to identify possible barriers hindering wider application of this approach. Methods Two HRQoL questionnaires (St. George's Respiratory Questionnaire SGRQ and EORTC QLQ-C30) were electronically presented on portable tablet computers. Wireless network (WLAN) integration into practice computer systems of 14 German general practices with varying infrastructure allowed automatic data exchange and the generation of a printout or a PDF file. General practitioners (GPs) and practice assistants were trained in a 1-hour course, after which they could invite patients with chronic diseases to fill in the electronic questionnaire during their waiting time. We surveyed patients, practice assistants and GPs regarding their acceptance of this tool in semi-structured telephone interviews. The number of assessments, HRQoL results and interview responses were analysed using quantitative and qualitative methods. Results Over the course of 1 year, 523 patients filled in the electronic questionnaires (1–5 times; 664 total assessments). On average, results showed specific HRQoL impairments, e.g. with respect to fatigue, pain and sleep disturbances. The number of electronic assessments varied substantially between practices. A total of 280 patients, 27 practice assistants and 17 GPs participated in the telephone interviews. Almost all GPs (16/17 = 94%; 95% CI = 73–99%), most practice assistants (19/27 = 70%; 95% CI = 50–86%) and the majority of patients (240/280 = 86%; 95% CI = 82–91%) indicated that they would welcome the use of electronic HRQoL questionnaires in the future. GPs mentioned availability of local health services (e.g. supportive, physiotherapy) (mean: 9.4 ± 1.0 SD; scale: 1 – 10), sufficient extra time (8.9 ± 1.5) and easy interpretation of HRQoL results (8.6 ± 1.6) as the most important prerequisites for their use. They believed HRQoL assessment facilitated both communication and follow up of patients' conditions. Practice assistants emphasised that this process demonstrated an extra commitment to patient centred care; patients viewed it as a tool, which contributed to the physicians' understanding of their personal condition and circumstances. Conclusion This pilot study indicates that electronic HRQoL assessment is technically feasible in general practices. It can provide clinically significant information, which can either be used in the consultation for routine care, or for research purposes. While GPs, practice assistants and patients were generally positive about the electronic procedure, several barriers (e.g. practices' lack of time and routine in HRQoL assessment) need to be overcome to enable broader application of electronic questionnaires in every day medical practice.